TEKNIK MENYARING INFORMASI INTERNET UNTUK MENDAPATKAN MATERI BELAJAR - ADRIYENDI, ADRIYENDI (IAIN Batusangkar, 2010)
A important component of teaching learning process is teaching material. A good teaching material will produce optimal and new (recent) teaching learning process. Internet is a source where we can find and get the new teaching recently. To find the teaching material, we have to know the computer identity where the teaching material is located. The Internet can be categories into 2 categories namely edu (education) for computer which located in United State and ac (academic) which is followed by country code for computer which located in the outside of United State. Filtering information with Search Engine include Power Searching Conceptual with application need technique for get information is expected. Key words: filter, information, website, teaching material, find and get